The clinical significance and prognostic value of early second peak of hs-troponin t in patients successfully treated with primary pci. (25th November 2020) - Ohtaroglu, K; Durmaz, E; Karadag, B; Raimoglu, U; Mutlu, D; Tokdil, H; Karaca, O; Polat, F; Ozmen, E; Koca, D; Incesu, G; Ongen, Z
Abstract: Background: It was previously demonstrated that in patients with ST segment elevation myocardial infarction (STEMI) high-sensitive troponin-T (Hs-cTnT) makes two peaks. However, the clinical significance of the second peak (early vs late) in patients undergoing successful primary percutaneous intervention (pPCI) is not known. We investigated the role of early second peak on clinical outcomes. Methods: Patients who underwent successful pPCI were included. Baseline characteristics, angiographic variables and kinetics of Hs-cTnT levels following pPCI were recorded. Second peak of Hs-cTnT was defined as re-elevation of troponin levels above plateau levels. The second peak of Hs-cTnT is defined as early second peak, if re-elevation is detected earlier than 72 hours after the diagnosis and late second peak, when re-elevation is detected later than 72 hours. Results: We included 250 patients divided into two groups; patients with early second peak as group 1 (n=118) and rest of the patients as group 2 (n=132). Baseline characteristics and comorbidities were similar. Peak level of Hs-cTnT, Hs-CRP and pro-BNP levels were significantly lower in group 1 patients. Left ventricular ejection fraction was higher in group 1 patients (47.48±7.7 vs 43.80±9.3, p-value: 0.001). There was no significant difference with respect to new-onset heart failure (24% vs %28, p: 0.503) between groups however cardiac mortality was significantly lower in group 1 patients (%2 vs %11, p: 0.007). Conclusion: The early second peak of Hs-cTnT in patients with STEMI is associated with successful reperfusion and predictors of better clinical outcome. Moreover, early second peak of Hs-cTnT is associated with decreased cardiac mortality and has a potential to be used as a marker of good prognosis. Funding Acknowledgement: Type of funding source: None